Hubungan Jumlah Pengeluaran Keluarga dengan Status Pertumbuhan Bayi di Kecamatan Imogiri - Retno Egha Adifa; Pramitha Sari; Herni Dwi Herawati; Wiji Indah Lestari (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Child growth issues such as stunting, underweight, wasting, and overweight remain serious health problems in Indonesia. The prevalence of growth issues remains high, with 15.9% being underweight, 8.5% being wasted, and 22.1% being stunted. One factor influencing infant growth is family spending on nutrition and healthcare. This study aims to analyze the relationship between the amount of family expenditure and the growth status of infants aged 6-12 months in Imogiri District, Bantul Regency, Special Region of Yogyakarta. This study used a quantitative approach with a cross-sectional design. This study was conducted in Imogiri District, Bantul Regency, Yogyakarta Special Region. The sample in this study were mothers with babies aged 6-12 months, totaling 163 respondents and selected using a purposive sampling technique. Data were collected through a questionnaire regarding the amount of family expenditure, both food and non-food, each month, and an analysis of infant growth status based on the infant growth status chart in the Child Health Card (KMS) according to weight/age for babies aged 6-12 months in the Maternal and Child Health Book (KIA). The data analysis technique used the Chi-Square test. Based on the Chi-Square Test, it shows a significant relationship between family expenditure and the growth of infants aged 6–12 months (p = 0.015), where infants from high-expenditure families have a 3.27 times greater chance (OR) of experiencing increased growth status. There is a significant relationship between the amount of family expenditure and the growth status of infants aged 6-12 months in Imogiri District.